P206 A study to investigate the mechanisms underlying circadian rhythm in asthma. (15th November 2017) - Durrington, HJ; Krakowiak, K; Singh, D; Ray, D
Abstract : Background: Time of day is critical in the pathogenesis of asthma, and has been realised for centuries. Symptoms of asthma are worse around 4 am, when airway restriction is at its highest. Many asthma treatments are taken in the morning or evening, however there is increasing data that steroids are more efficacious if taken mid-afternoon. Investigating the biological timing of asthma is crucial to better understand the pathogenesis of asthma, this may lead to the discovery of new drug targets, and the identification of dynamic biomarkers that change by time of day and would be useful in a future chronotherapeutics study. Aims: Define new biochemical pathways involved in the circadian variation in asthma Determine a circadian biomarker in asthma Method: We recruited 10 atopic, moderately severe asthmatics and 10 healthy volunteers to complete 4 study visits, including an overnight stay. Blood, induced sputum and breath were sampled at intervals throughout the day and night, and physiological measurements made. PBMCs were harvested from peripheral blood at 4 am and 4 pm and plated in 6 groups, control, +LPS/anti-CD3/anti CD28, +P38 i, +LPS/anti-CD3/anti CD28 +P381, +Dexamethasone, +LPS/anti-CD3/anti CD28 +dexamethasone for 2 hours. Conditioned medium was collected and frozen at −80, cell lysates were prepared for RNA extraction, and protein purification. Reference: 14/NW/1352. Results: There is a high amplitude circadian change in FEV1 in asthmatics compared to healthy controls. The nadir is at 4 am (figure 1 ). There was also an increase in sputum and serum eosinophils (a key effector cell in asthma) at 4 am compared to 4 pm in asthmatics (figure 1 ). On-going workflow includes: Transcript measurement from PBMCs using a combination of RNA-Sequencing and nanostring technology (for clock genes; inflammatory mediators; Signalling regulators; MAP kinase family members) Bioplex screen for expression and activation of additional MAPkinase components, and IkBa, from protein extracts and conditioned media Lipidomic analyses of serial, matched serum samples will allow analysis of the ceramide/sphingolipid pathway Breathomics analysis for volatile organic compounds in serial, matched breath samples. Discussion: We have demonstrated a significant diurnal effect on asthma lung physiology and eosinophil profiles. Further downstream analysis of serum, breath and sputum is underway.